Bibliometric Analysis of the Spontaneous Group Discussion Method of Learning Mathematics Using Vosviewer Software - Desiana Desiana; Joko Soebagyo (Universitas Pendidikan Mandalika, 2022)
The purpose of this study is to identify themes related to the spontaneous group discussion method so that it can be used as an opportunity for further research on the method of spontaneous group discussion in learning mathematics. This research method uses bibliometric analysis method. Data collection was taken from the Google Scholar database through the PoP (Publish or Perish) application with the keywords spontaneous group discussion mathematical method and processed using VOSviewer software. Most spontaneous group discussion research publications occurred in 2020 and 2021 as many as 31 articles. Analysis of the data in this study using VOSViewer software. The results of this study indicate that Spontaneous group discussions that are still rarely carried out include cases study, creativity and implementation. The spontaneous group discussion method can increase students' knowledge, creativity, and application of learning methods so that the objectives of learning activities can be achieved.